Identification of fungus-growing termite-associated halogenated-PKS maduralactomycin a as a potential inhibitor of MurF protein of multidrug-resistant Acinetobacter baumannii - Shoaib, Muhammad; Shehzadi, Iram; Asif, Muhammad Umair; Shen, Yulong; Ni, Jinfeng (Frontiers in Molecular Biosciences, 2023)
Multidrug-resistant Acinetobacter baumannii infections have become a major public health concern globally. Inhibition of its essential MurF protein has been proposed as a potential target for broad-spectrum drugs. This study aimed to evaluate the potential of a novel ecological niche of 374 fungal-associated termite-derived natural products (NPs). The molecular docking and computational pharmacokinetics screened four compounds, i.e., Termstrin B, Fridamycin A, Maduralactomycin A, and Natalenamide C, as potential compounds that have higher binding affinities and favourable protein-ligand interactions. The compound Maduralactomycin A induced more stability based on its lowest average RMSD value (2.31 Å) and low standard deviation (0.35) supported by the consistent flexibility and β-factor during the protein's time-dependent motion. While hydrogen bond analysis indicated that Termstrin B has formed the strongest intra-protein interaction, solvent accessibility was in good agreement with Maduralactomycin A compactness.Maduralactomycin A has the strongest binding energy among all the compounds (-348.48 kcal/mol), followed by Termstrin B (-321.19 kcal/mol). Since these findings suggest Maduralactomycin A and Termstrin B as promising candidates for inhibition of MurF protein, the favourable binding energies of Maduralactomycin A make it a more important compound to warrant further investigation. However, experimental validation using animal models and clinical trials is recommended before reaching any final conclusions.